2022
DOI: 10.1186/s40359-022-00828-2
|View full text |Cite
|
Sign up to set email alerts
|

The associations between caregivers’ psychosocial characteristics and caregivers’ depressive symptoms in stroke settings: a cohort study

Abstract: Background Studies have found that caregivers can influence stroke survivors’ outcomes, such as mortality. It is thus pertinent to identify significant factors associated with caregivers’ outcomes. The study objective was to examine the associations between caregivers’ psychosocial characteristics and caregivers’ depressive symptoms. Methods The analysis obtained three-month and one-year post-stroke data from the Singapore Stroke Study, which was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Notably, the results of the present study showed that there is a statistically significant and inverse relationship between care burden and depressive symptoms in family caregivers. Our findings support previous research ( 64 , 65 ) suggesting that caregivers who score high care burden have also high depression. Despite these similar findings in the literature, we don't see a ready explanation for this association.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the results of the present study showed that there is a statistically significant and inverse relationship between care burden and depressive symptoms in family caregivers. Our findings support previous research ( 64 , 65 ) suggesting that caregivers who score high care burden have also high depression. Despite these similar findings in the literature, we don't see a ready explanation for this association.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers report that caregivers with moderate to high levels of subjective burden experience or are at high risk for developing depressive symptoms [ 34 , 41 , 51 ] and exhibit emotional changes [ 19 ]. In addition, a cohort study by Koh and his colleagues [ 48 ] showed that caregivers who mentioned that were burdened by their caregiving responsibilities had high depression scores when their depressive symptoms were measured three months after the patient’s stroke. These scores appeared to decrease statistically significantly when assessed one year after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was found that caregivers’ high level of benefit finding could predict low levels of anxiety, depression, and burden [ 57 ]. Additionally, a study by Koh et al [ 48 ] found that levels of depression decreased statistically significantly over a 9-month period. As previously mentioned for this study, caregivers’ depressive symptom assessments were conducted at 3 and 12 months after the patient’s stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations